Sodium Ascorbate as a Quorum-Sensing Inhibitor Leads to Decreased Virulence in Vibrio campbellii - Han, Biao; Zheng, Xiaoting; Baruah, Kartik; Bossier, Peter (Frontiers in Microbiology, 2020)
Vibrio campbellii is one of the major bacterial pathogens for animals reared in aquaculture, affecting both vertebrates and invertebrates, and causes significant economic losses. It is now evident that the expressions of virulence factors in this pathogen are regulated by the density of the bacterial population. This type of regulation, termed quorum sensing (QS), is mediated by extracellular signal molecules called autoinducers. In this study, the impact of sodium ascorbate (NaAs) on the virulence of V. campbellii was investigated under both in vitro and in vivo conditions, to develop a natural anti-infective strategy to contain V. campbellii infection in aquacultured animals. Results showed that NaAs significantly decreased swimming motility, biofilm production, and the production of virulence enzymes, such as lipase, caseinase, phospholipase, and hemolysin in V. campbellii. Consistent with this, pretreatment of V. campbellii with NaAs before inoculation into the rearing water resulted in significantly increased survival of gnotobiotic brine shrimp larvae, when compared to larvae challenged with untreated V. campbellii. Furthermore, NaAs could interfere with QS-regulated bioluminescence in V. campbellii, suggesting the QS-inhibitory activity largely determines the protective effect of NaAs towards the brine shrimp. In essence, due to the potent anti-virulence effects observed in in vitro studies and the clinical brine shrimp-V. campbellii infection model, NaAs constitute a promising novel strategy for the control of V. campbellii infections in aquaculture.